Neurological Symptoms in Coronavirus Disease 2019 Patients: An Updated Literature Review - Jafarinia, Morteza; Mohammadi, Somayeh; Rostami, Amirabbas; Naghdizadeh, Fateme; ShojaeiBaghini, Mahdie; Karami, Nooshin; Negargar, Sohrab; Emadi, Mohsen (Galen Medical Journal, 2022)
Several studies have reported that coronavirus disease 2019 (COVID-19) can lead to multi-organ dysfunction. COVID-19 has been linked to a variety of neurological symptoms, according to the literature. The various paths via which the brain can be infected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), as well as the symptoms of COVID-19 in neurological diseases, are discussed. COVID-19 symptoms have been observed in neurological illnesses such as epilepsy, ischemic stroke, multiple sclerosis, Alzheimer's disease, subarachnoid hemorrhage, Guillainâ€“BarrÃ© syndrome, and Parkinson's disease in several investigations.